Factors contributing to the performance of Small and Medium Enterprises in the Capricorn District Municipality, Limpopo Province - Rameetse, Mapelo Rosah (My University, 2025)
Small and Medium Enterprises (SMEs) are widely recognized as key drivers of economic growth and job creation both in South Africa and globally. However, most of them do not grow or survive in the long term. The owners struggle with effective management skills and risk management, which is why many of them fail. SMEs often face operational inefficiencies and have less structured management practices such as risk management. This is because most of them were started for survival purposes. The researcher has observed that most of the SMEs have difficulties in retaining and attracting skilled workers. This is due to fewer resources for training and a knowledge shortage on which platforms to use. The primary aim of this project was to explore the factors contributing to the performance of SMEs in the Capricorn District Municipality, Limpopo province. The quantitative research approach was employed, utilizing self-administered questionnaires to gather data from SME owners/managers. Out of a total of 130 distributed questionnaires, 110 were returned. The questionnaire consisted of five sections: demographic information, profile of business activities, risk management competencies, financial decision-making capabilities and SME performance. Data analysis was analyzed using the Statistical Package for the Social Sciences (SPSS) version 24, with diagrams generated to present the findings. Inferential statistics and Pearson correlation analysis were used to test relationships among risk management, financial decision-making competencies, and SME performance in Capricorn District Municipality, Limpopo Province. The internal consistency and reliability of the nominal and ordinal variables were assessed using Cronbach’s alpha. Validity was ensured through the development of the questionnaire based on theoretical foundations, and a pilot study was conducted with five SMEs to pre-test the instrument. Both content and face validity were confirmed by pre-testing and academic review of the questionnaire. The risk management competencies required in SMEs were determined to be behavioural and technical competencies. The financial decision-making competencies were found to be capital budgeting techniques, liquidity ratios, cash and accrual accounting, and working capital management. The study revealed that the decisions that SME managers/owners take can negatively or positively affect the business, hence understanding the mentioned competencies can help drive the business to success. The findings were that most of the respondents did not know about or benefit from the government’s support programs. Additionally, most SMEs did not have risk management policies and contingency plans. The recommendations proposed included the mandatory submission of risk management policy and financial contingency plan documents when SMEs register their businesses with the CIPC to help reduce high failure rates.
Thesis (M. Com. (Business Management)) -- University of Limpopo, 2025
Keywords: Risk management; Financial decision-making; Competencies; Performance; SME; Business enterprises -- South Africa; Business enterprises -- Size; Business enterprises -- Finance; Small business -- South Africa -- Limpopo